Reasons for initiating long-acting antipsychotics in psychiatric practice: findings from the STAR Network Depot Study. (December 2020) - Barbui, Corrado; Bertolini, Federico; Bartoli, Francesco; Calandra, Carmela; Callegari, Camilla; Carrà, Giuseppe; D'Agostino, Armando; Lucii, Claudio; Martinotti, Giovanni; Mastromo, Daniele; Moretti, Daniele; Monzani, Emiliano; et al.
Background: Long acting injectable (LAI) antipsychotics have been claimed to ensure treatment adherence and possibly reduce the daily burden of oral formulations. So far, only surveys investigating the theoretical prescribing attitudes of clinicians have been employed. On this basis, we aimed to investigate reasons for prescribing LAIs in a real-world, unselected sample of patients. Methods: The STAR Network Depot Study is an observational, multicentre study consecutively enrolling adults initiating a LAI over a 12-months period. Clinical severity was assessed with the Brief Psychiatric Rating Scale, and patient's attitude toward medications with the Drug Attitude Inventory 10 items. Psychiatrists recorded reasons for LAI prescribing for each study participant. Responses were grouped into six non-mutually exclusive categories: aggressiveness, patient engagement, ease of drug taking, side-effects, stigma, adherence. Results: Of the 451 patients included, two-thirds suffered from chronic psychoses. Improving patient engagement with the outpatient psychiatric service was the most common reason for prescribing LAIs (almost 80% of participants), followed by increasing treatment adherence (57%), decreasing aggressiveness (54%), and improving ease of drug taking (52%). After adjusting for confounders, logistic regression analyses showed that reasons for LAI use were associated with LAI choice (e.g. first-generation LAIs for reducing aggressiveness). Conclusion: Despite the wide availability of novel LAI formulation and the emphasis on their wider use, our data suggest that the main reasons for LAI use have remained substantially unchanged over the years, focusing mostly on improving patient's engagement. Further, clinicians follow implicit prescribing patterns when choosing LAIs, and this may generate hypotheses for future experimental studies.